056 Subcutaneous Testosterone Enanthate-Autoinjector: Assessment of its Post-Market Safety and Efficacy Profiles. (1st May 2022) - Choi, E.; Xu, P.; El-Khatib, F.; Kavoussi, P.; Yafi, F.
ABSTRACT: Introduction and Objective: A subcutaneous testosterone enanthate-autoinjector (SCTE-AI) was recently approved by the Food and Drug Administration in 2018 for patient-administered weekly testosterone replacement therapy (TRT). This is the largest non-industry sponsored post-market study to evaluate the safety and efficacy profile of SCTE-AI in outpatient urology clinics. Methods: From January to October 2019, 110 hypogonadal men were treated with SCTE-AI at a two-institutions. Patients were assessed in a pre-therapy visit prior to receiving SCTE-AI and re-assessed at 6-weeks after treatment initiation. Patients with a history of prostate cancer were excluded. Trough serum total testosterone (TT), estradiol, prostate-specific antigen (PSA), and hematocrit (HCT) levels were collected at clinic visits. Therapeutic phlebotomy was recommended for HCT>54%, and treatment was discontinued for significant increases in PSA and for significant treatment-related adverse events. Values from each visit were compared with univariate analysis. Results: 110 patients completed the 6 weeks of observation with a mean age of 40.3 (SD: 10.5). TT significantly rose from 246.6 ng/dL (SD:113.3) pretherapy to 538.4 ng/dL (SD: 209.3) at 6 weeks (p<0.001). Post-therapy, 101/110 (91.8%) of patients had TT>300 ng/dL. No patients had HCT > 54%. 74 patients (70.5%) had PSA increase with only 3 (2.9%) experiencing an increase >1.0 ng/dL. There was a significant increase in mean PSA from 1.07 ng/dL (SD: 0.8) pretherapy to 1.18 ng/dL (SD: 0.9) at 6 weeks (p= 0.01). One patient had immediate treatment cessation following diagnosis of prostate cancer. Conclusions: This is the largest non-industry sponsored safety and efficacy profile of SCTE-AI application in urology clinics. After 6 weeks of observation, TT levels increased significantly. SCTE-AI is a safe and effective alternative method for TRT. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (Antares Pharma, Clarus Therapeutics, Coloplast, Promescent, Viome).